2018
DOI: 10.1111/cxo.12630
|View full text |Cite
|
Sign up to set email alerts
|

Contrast‐balanced binocular treatment in children with deprivation amblyopia

Abstract: These data suggest that supervised contrast-balanced binocular treatment should be further investigated as a treatment option for children with deprivation amblyopia. However, for children with more severe deprivation amblyopia due to early unilateral cataracts, supplementary or alternative options should also be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 66 publications
0
14
0
1
Order By: Relevance
“…Previously, in a smaller group of 28 children, between 5 and 14 years old, was evaluated (18 with deprivation amblyopia, 8 with anisometropic amblyopia, and 2 with mixed anisometropic and strabismic amblyopia) [ 45 ]. Visual acuity was assessed after a 6 weeks period using the falling blocks game 1 h per day.…”
Section: Modern Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, in a smaller group of 28 children, between 5 and 14 years old, was evaluated (18 with deprivation amblyopia, 8 with anisometropic amblyopia, and 2 with mixed anisometropic and strabismic amblyopia) [ 45 ]. Visual acuity was assessed after a 6 weeks period using the falling blocks game 1 h per day.…”
Section: Modern Treatmentsmentioning
confidence: 99%
“…Gao et al [ 44 ] almost found the same improvement in the placebo group than in the active group. Hamm et al [ 45 ] found an improvement that might be similar to test–retest repeatability —less than 1.5 logMAR lines—and may not be clinically significant for amblyopes [ 47 ]. In addition, Manh et al [ 46 ] showed that patching was more effective than treatment with falling blocks.…”
Section: Modern Treatmentsmentioning
confidence: 99%
“…This project was a first step towards understanding how the medical community could improve provision of treatment for childhood cataract. The project was part of a larger study about the consequences of,44 and potential for rehabilitation after45 visual deprivation due to childhood cataract. A lay summary of results will be available to all participants, and information will also be disseminated at a community follow-up meeting or ‘hui’.…”
Section: Methodsmentioning
confidence: 99%
“…The management of such condition too need a lot of attention and less successful compared to other forms of amblyopia. It effects all other visual functions as well [42] [43] [44] [45].…”
Section: Types Of Amblyopiamentioning
confidence: 99%